Element-element chemical bond in compounds of group 14; The 15th International Congress of Quantum Chemistry (ICQC), June 8-13, 2015, Beijing, China; Poster_session 4 - Poleshchuk O. Kh. Oleg Khemovich (2015, 2015)
Title screen